A systematic review on factors influencing watching movies online among youth - Yening, Yang; Ahmad Ghazali, Akmar Hayati; Shari, Sharil Nizam (Human Resource Management Academic Research Society (HRMARS), 2023)
With the advancement of Internet technology, streaming media platforms act as an increasingly important role in providing online services to film audiences. There are many relevant studies on audiences' preferences between cinema and online platforms, but very little research focus on youth. The limited number of systematic review articles on online movie viewing among youth allows this article to analyze the existing literature systematically. This study was guided by the PRISMA statement and based on the systematic review on Scopus and ScienceDirect, this study selects a total of 23 related articles, which were resulted in five main themes, namely content, technology, social, environment, and emotional participation. Future studies are suggested to concentrate on the interview method or mixed method and try to involve experts for synergistic validation when identifying topics in this study.